Review of proximal splenic artery embolization in blunt abdominal trauma - Keith Bertram Quencer (CVIR Endovascular, 2019)
Abstract The spleen is the most commonly injured organ in blunt abdominal trauma. Unstable patients undergo laparotomy and splenectomy. Stable patients with lower grade injuries are treated conservatively; those stable patients with moderate to severe splenic injuries (grade III-V) benefit from endovascular splenic artery embolization. Two widely used embolization approaches are proximal and distal splenic artery embolization. Proximal splenic artery embolization decreases the perfusion pressure in the spleen but allows for viability of the spleen to be maintained via collateral pathways. Distal embolization can be used in cases of focal injury. In this article we review relevant literature on splenic embolization indication, and technique, comparing and contrasting proximal and distal embolization. Additionally, we review relevant anatomy and discuss collateral perfusion pathways following proximal embolization. Finally, we review potential complications of splenic artery embolization.